2011
DOI: 10.4070/kcj.2011.41.4.184
|View full text |Cite
|
Sign up to set email alerts
|

Decreased Glomerular Filtration Rate is an Independent Predictor of In-Hospital Mortality in Patients With ST-Segment Elevation Myocardial Infarction Undergoing Primary Percutaneous Coronary Intervention

Abstract: Background and ObjectivesPatients with renal dysfunction (RD) experience worse prognosis after myocardial infarction (MI). The aim of the present study was to investigate the impact of admission estimated glomerular filtration rate (eGFR) on clinical outcomes of patients undergoing primary percutaneous coronary intervention (PCI) for ST-segment elevation MI (STEMI).Subjects and MethodsWe retrospectively evaluated 4,542 eligible patients from the Korea Acute Myocardial Infarction Registry (KAMIR). Patients were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 30 publications
2
17
0
Order By: Relevance
“…Model 2 included left ventricular ejection fraction (LVEF) in addition to the covariates in model 1 to reflect severity of infarction and/or baseline cardiac function at index admission. Model 3 included estimated glomerular filtration rate (eGFR), calculated from serum creatinine levels using the prediction equation from the Modification of Diet in Renal Disease Study Group [10] in addition to the covariates in model 2 because renal dysfunction was also assessed as an independent prognostic factor in previous studies [11,12]. All statistical procedures were performed using the PASW software version 18.0 (IBM Co., Armonk, NY, USA).…”
Section: Methodsmentioning
confidence: 99%
“…Model 2 included left ventricular ejection fraction (LVEF) in addition to the covariates in model 1 to reflect severity of infarction and/or baseline cardiac function at index admission. Model 3 included estimated glomerular filtration rate (eGFR), calculated from serum creatinine levels using the prediction equation from the Modification of Diet in Renal Disease Study Group [10] in addition to the covariates in model 2 because renal dysfunction was also assessed as an independent prognostic factor in previous studies [11,12]. All statistical procedures were performed using the PASW software version 18.0 (IBM Co., Armonk, NY, USA).…”
Section: Methodsmentioning
confidence: 99%
“…Chronic kidney disease, even mild, is associated with increased cardiovascular mortality [9]. More recently it was demonstrated that renal dysfunction is independently associated with in-hospital mortality in STEMI patients treated with pPCI [10-12]. …”
Section: Introductionmentioning
confidence: 99%
“…Renal dysfunction is an independent risk factor for death in patients with STEMI [ 27 ]. And patients with renal dysfunction have been shown to have a 6 to 11-fold higher in-hospital mortality rate compared to patients with normal renal function [ 8 ]. These patients more commonly developed low left ventricular ejection fraction, higher Killip class, cardiogenic shock, hemodynamic instability or malignant arrhythmia during admission [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Widely used early reperfusion therapy, including emergency primary percutaneous coronary intervention (PCI) or thrombolysis therapy has beneficial effects for STEMI [ 3 , 4 ]. However, RI following STEMI is associated with a worse clinical prognosis [ 5 7 ], a 6 to 11-fold increase in hospital risk of death [ 8 ], and a 1.76- to 6.18-fold 7-month risk of death [ 6 ]. Unfortunately, most STEMI patients with RI are excluded from randomized trials.…”
Section: Introductionmentioning
confidence: 99%